UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA MELALUI PENDEKATAN OPEN-ENDED - Indrie Noor Aini (Department of Mathematics Education, Universitas Kuningan, 2016)
Problem solving is a process to fix the difficulties encountered the achievement a goal to be achieved. To improve the ability of problem solving mathematical, one of them by learning to use the Open-Ended approach. Open-Ended approach to discuss and solve problems with the assumption that the process is more important than the result. Open-Ended approach gives flexibility to the student to put the answer. This study aims to improve students' mathematical problem solving ability after using the Open-Ended approach. To lead to these objectives, this study examines the mathematical problem solving ability of students in mathematics learning with the Open-Ended approach in every cycle. This research was conducted by the method of action research with research subjects students of class IX MTs Special Program. Darussalam Ciamis, the number of students as subject is 22 students. The instrument used in this study is the observation sheet that covers the activities of teachers and students; formative test and posttest to measure students' mathematical problem solving ability. The results of this study are mathematical problem solving ability of students in each cycle is good, as well as the completeness of classical study categorized either. Keywords : problem-solving ability, Open-Ended approach.